The Molecular Virology of Hepatitis B Virus - Glebe, Dieter; Bremer, Corinna M. (Seminars in Liver Disease, 2013)
Hepatitis B virus (HBV) is one of the smallest enveloped DNA viruses and the prototype member of the family of Hepadnaviridae that causes acute and chronic infections of mammals (including human) and birds. HBV has evolved an extreme adaptation and dependency to differentiated hepatocytes of its host. Despite its very limited coding capacity with only four open-reading frames, HBV is able to evade the immune system of the host and persist lifelong within infected hepatocytes. During active replication, HBV produces enormous viral loads in the blood and a massive surplus of subviral surface antigen particles in the serum of infected patients without killing their hepatocytes. Together with the use of a reverse transcriptase during replication, it provides an enormous genetic flexibility for selection of viral mutants upon selective pressure, for example, by the immune system or antiviral therapy. In addition, viral wild-type and mutated genomes are stably archived in the nucleus of the infected hepatocyte in an episomal DNA form that provides independence from cellular replication or integration within the host genome. We are just beginning to understand the delicate molecular and cellular interactions during the HBV replicative cycle within infected hepatocytes, so further studies are urgently needed to provide a better basis for further diagnostic and therapeutic options.
Keywords: hepatitis B virus; receptor; viral entry; sodium taurocholate cotransporting polypeptide; replication; cccDNA